The Relationship between Attitudes and Actions on the Successful Implementation of Community-Based Total Sanitation Programs in the Coastal Areas of the Konawe Islands Regency - Reinaldy Juliansyah, Muhammad; Azizi Jayadipraja, Erwin; Aziz Harun, Abdul (Waluya The International Science of Health Journal, 2023)
Introduction: The successful implementation of a community-based total sanitation program is greatly influenced by the attitudes and actions adopted by the community. This study aims to determine the relationship between attitudes and actions towards the successful implementation of a community-based total sanitation program in the coastal area of ​​Konawe Kepulauan Regency. Method: The data used is the chi-square statistical test to determine the relationship between attitudes and actions on the successful implementation of a community-based total sanitation program in the coastal area of ​​Konawe Kepulauan Regency. Result: This research was conducted in the working area of ​​6 Community Health Centers in Konawe Kepulauan Regency. Sanitation is very important to support one's health, so people must be able to apply sanitation in their daily lives. In the analysis of the chi-square test, it was found that attitudes sufficiently influenced the successful implementation of the CBTS program by 51.8% and actions that sufficiently influenced the successful implementation of the CBTS program by 53.0%. Conclusion: The conclusion in this journal is that attitudes are related to the successful implementation of the CBTS program and actions are related to the successful implementation of the CBTS program. This research raises awareness that attitudes and actions towards good sanitation can improve the quality of public health status and can increase the success of community-based total sanitation programs in Konawe Kepulauan Regency.